FASCIOLIASIS - A CAUSE OF OBSTRUCTIVE JAUNDICE: A CASE REPORT - Shah, Sayed Agha Ali; Khan, Muhammad Yasin; Ahmad, Jamil (Journal of Postgraduate Medical Institute, 2011)
A rare case of obstructive Jaundice in a 35 yrs old male from Afghanistan is presented with recurring attacks of upper abdominal pain and jaundice. Ultrasound examination revealed multiple gallstones with dilated common bile duct. During exploration of common bile duct, five leaf like liver flukes(Fasciola Hepatica) were recovered and identified. Patient was treated with Albendazole and had an uneventful recovery. Biliary fascioliasis should be considered in the differential diagnosis of obstructive jaundice.